1998
DOI: 10.1016/s0029-7844(98)00250-6
|View full text |Cite
|
Sign up to set email alerts
|

Fetal splenic size in anemia due to rh-alloimmunization

Abstract: Splenomegaly is sensitive for the detection of severe anemia in nonhydropic Rh sensitized cases without prior transfusion. The splenic enlargement could be explained by extramedullary erythropoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 9 publications
5
25
0
1
Order By: Relevance
“…Oepkes et al [8] found that splenic circumference was an excellent predictor of severe anemia (Hb deficit >5 SD from normal mean) in 44 of 47 cases, with a positive predictive value of 94%. However, though consistent with those in previous studies, our results indicated that splenic size measurement was not as excellent a predictor of anemia as seen in the reports of Oepkess et al [8] and Bahado-Singh et al [7] which was studied in late gestation. This may be due to the fact that splenic size at midpregnancy (18–22 weeks of gestation) may not be as sensitive in differentiating affected from unaffected fetuses as in later pregnancy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Oepkes et al [8] found that splenic circumference was an excellent predictor of severe anemia (Hb deficit >5 SD from normal mean) in 44 of 47 cases, with a positive predictive value of 94%. However, though consistent with those in previous studies, our results indicated that splenic size measurement was not as excellent a predictor of anemia as seen in the reports of Oepkess et al [8] and Bahado-Singh et al [7] which was studied in late gestation. This may be due to the fact that splenic size at midpregnancy (18–22 weeks of gestation) may not be as sensitive in differentiating affected from unaffected fetuses as in later pregnancy.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, theoretically, splenic size assessment may probably be effective in identifying fetal anemia. Previous studies showed that the splenic size was highly effective in identifying fetuses affected by Rh alloimmunization [7,8]. Oepkes et al [8] found that splenic circumference was an excellent predictor of severe anemia (Hb deficit >5 SD from normal mean) in 44 of 47 cases, with a positive predictive value of 94%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hemoglobin deficit was calculated based on the difference between the hemoglobin expected for the gestational age and that found in the puncture. IUT was performed when the fetal hemoglobin concentration deficit was ≥5 g/dL [12]. …”
Section: Methodsmentioning
confidence: 99%
“…The second criterion was proposed by Bahado-Singh et al, published in 1998 [12]. These authors also use the concept of hemoglobin deficit as a parameter to classify the severity of anemia.…”
Section: Introductionmentioning
confidence: 99%